Risk Factors and Outcomes of Hospitalized Patients With Severe Coronavirus Disease 2019 (COVID-19) and Secondary Bloodstream Infections: A Multicenter Case-Control Study. (20th November 2020) - Bhatt, Pinki J; Shiau, Stephanie; Brunetti, Luigi; Xie, Yingda; Solanki, Kinjal; Khalid, Shaza; Mohayya, Sana; Au, Pak Ho; Pham, Christopher; Uprety, Priyanka; Nahass, Ronald; Narayanan, Navaneeth
Abstract: Background: Coronavirus disease 2019 (COVID-19) has become a global pandemic. Clinical characteristics regarding secondary infections in patients with COVID-19 have been reported, but detailed microbiology, risk factors, and outcomes of secondary bloodstream infections (sBSIs) in patients with severe COVID-19 have not been well described. Methods: We performed a multicenter case-control study including all hospitalized patients diagnosed with severe COVID-19 and blood cultures drawn from 1 March 2020 to 7 May 2020 at 3 academic medical centers in New Jersey. Data collection included demographics, clinical and microbiologic variables, and patient outcomes. Risk factors and outcomes were compared between cases (sBSI) and controls (no sBSI). Results: A total of 375 hospitalized patients were included. There were 128 sBSIs during the hospitalization. For the first set of positive blood cultures, 117 (91.4%) were bacterial and 7 (5.5%) were fungal. Those with sBSI were more likely to have altered mental status, lower mean percentage oxygen saturation on room air, have septic shock, and be admitted to the intensive care unit compared with controls. In-hospital mortality was higher in those with an sBSI versus controls (53.1% vs 32.8%, P = .0001). Conclusions: We observed that hospitalized adult patients with severe COVID-19 and sBSI had a more severe initial presentation, prolonged hospital course, and worse clinical outcomes. To maintain antimicrobial stewardship principles, further prospective studies are necessary to better characterize risk factors and prediction modeling to better understand when to suspect and empirically treat for sBSIs in severe COVID-19. Abstract : Limited data are available regarding secondary bloodstream infections (sBSIs) in hospitalized patients with severe COVID-19. Patients with COVID-19 with sBSIs had more severe initial presentation, prolonged hospital course, and worse clinical outcomes compared with patients with COVID-19 without sBSIs.